Multiphoton microscopy imaging of fibrous meningiomas based on the combination of multichannel mode and lambda mode - You, Linghan; Shi, Linjing; Huang, Yuqing; Pan, Lingxin; Zheng, Shiying; Wang, Yingyuan; Wu, Zanyi; Wang, Xingfu; Chen, Jianxin; Fang, Na (Frontiers in Neuroscience, 2025)
Fibrous meningiomas, known for their dense and tough texture, present unique challenges in diagnosis and surgical treatment. This study explores the potential of multiphoton microscopy (MPM) for visualizing the microstructures of fibrous meningiomas by combining multichannel and lambda modes. Using MPM, we imaged 14 fibrous meningioma samples collected from neurosurgical procedures. The multichannel mode captured second harmonic generation (SHG) and two-photon excitation fluorescence (TPEF) signals, while the lambda mode provided detailed spectral imaging across 32 channels. Image analysis algorithms were developed to quantify collagen content and assess morphological features. Spectroscopic analysis revealed the intrinsic components of fibrous meningiomas, with collagen being the most abundant component (relative ratio: 0.952), followed by structural proteins (0.502), free-form NADH (0.393), FAD (0.199), lipopigments (0.198), protein-bound NADH (0.105), porphyrin derivatives I (0.104), and porphyrin derivatives II (0.015). The combined spectral images also provided high-contrast and high-resolution views of the tumor microenvironment. Quantitative analysis showed that the average collagen content in fibrous meningioma tissues was 0.537 ± 0.131 using SHG imaging and 0.503 ± 0.133 using combined 32-channel spectral imaging. With the advancement of fiber optic technology and multiphoton endoscopy, multiphoton microscopy holds promise as a new technology for clinically diagnosing fibrous meningiomas.